Stress-induced changes in cognitive function and intestinal barrier integrity can be ameliorated by venlafaxine and synbiotic supplementations - Sarawut Lapmanee; Nattapon Supkamonseni; Sakkarin Bhubhanil; Nattakan Treesaksrisakul; Chaiyos Sirithanakorn; Mattaka Khongkow; Katawut Namdee; Piyaporn Surinlert; Chittipong Tipbunjong; Prapimpun Wongchitrat (PeerJ, 2024)
Stress profoundly impacts various aspects of both physical and psychological well-being. Our previous study demonstrated that venlafaxine (Vlx) and synbiotic (Syn) treatment attenuated learned fear-like behavior and recognition memory impairment in immobilized-stressed rats. In this study, we further investigated the physical, behavior, and cellular mechanisms underlying the effects of Syn and/or Vlx treatment on brain and intestinal functions in stressed rats. Adult male Wistar rats, aged 8 weeks old were subjected to 14 days of immobilization stress showed a decrease in body weight gain and food intake as well as an increase in water consumption, urinary corticosterone levels, and adrenal gland weight. Supplementation of Syn and/or Vlx in stressed rats resulted in mitigation of weight loss, restoration of normal food and fluid intake, and normalization of corticosterone levels. Behavioral analysis showed that treatment with Syn and/or Vlx enhanced depressive-like behaviors and improved spatial learning-memory impairment in stressed rats. Hippocampal dentate gyrus showed stress-induced neuronal cell death, which was attenuated by Syn and/or Vlx treatment. Stress-induced ileum inflammation and increased intestinal permeability were both effectively reduced by the supplementation of Syn. In addition, Syn and Vlx partly contributed to affecting the expression of the glial cell-derived neurotrophic factor in the hippocampus and intestines of stressed rats, suggesting particularly protective effects on both the gut barrier and the brain. This study highlights the intricate interplay between stress physiological responses in the brain and gut. Syn intervention alleviate stress-induced neuronal cell death and modulate depression- and memory impairment-like behaviors, and improve stress-induced gut barrier dysfunction which were similar to those of Vlx. These findings enhance our understanding of stress-related health conditions and suggest the synbiotic intervention may be a promising approach to ameliorate deleterious effects of stress on the gut-brain axis.
Keywords: Stress Responses and Cortisol; Tryptophan and brain disorders; Gut microbiota and health